ZOLEDRONIC ACID: A MISCHIEVOUS SUSPECT FOR LIVER INJURY - Gill, Rupam; O., Balaji; Kumari, Meena K.; V., Amberkar Mohan Babu; Udupa, Karthik S. (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT A 47-year-old male diagnosed as adenocarcinoma of the lung and received 8 cycles of chemotherapy comprising intravenous administration of cisplatin 125 mg, pemetrexed 850 mg along with zoledronic acid 4 mg. After the completion of the 8 cycle, the liver enzymes were found to be markedly elevated, evincing zoledronic acid as the cause for hepatotoxicity. The case details were taken from the patient’s medical record along with the biochemical test reports and radiographic images. The causal association was confirmed using Naranjo’s algorithm and Roussel Uclaf Causality Assessment Method (RUCAM). After the uneventful chemotherapy, patient’s liver function tests (LFT) were abnormal. There was an elevation in the aspartate aminotransferase, alanine transaminase, alkaline phosphatase, and direct bilirubin. The causal relationship was established using Naranjo’s algorithm (score-6) and RUCAM (score-5), displayed a probableâ€ and possibleâ€ association. Hartwig’s severity scale and Thornton’s preventability scale displayed the adverse drug reaction to being moderately severe and not preventable, respectively. The zoledronic acid was stopped and never readministered. The LFTs assumed normal after a span of 2 months. The mechanism underlying hepatotoxicity due to zoledronic acid remains elusive. Zoledronic acid can induce acute phase response mediated by active production of interleukin-6, tumor necrosis factor alpha, and pro-inflammatory cytokines from the T-cells and macrophages. Vigilant monitoring along with timely assessment and management can prevent the occurrence of irreversible liver damage. Henceforth, we would like to report the rare incidence of drug induced hepatic damage due to zoledronic acid. Henceforth, we would like to report the rare incidence of drug induced hepatic damage due to zoledronic acid. Keywords: Bisphosphonate, Dechallenge, Hepatotoxicity, Rechallenge. th